The Existence of the "Mbeleh Golekan" Tradition in Kandangan Village, Kediri - Paramita, Virgin Diana (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
The mbeleh golekan tradition in Kandangan Village is a variety of village clean traditions in Java. Writing this article aims to analyze the existence of the mbeleh golekan tradition, whose ritual is very different from most other village clean tradition rituals. Where the discussion of this article covers the history of the emergence of the mbeleh golekan tradition, the processions and rituals carried out during this tradition, and the meaning of the symbols in it. The tradition of mbeleh golekan has been attached and an inseparable part of local people’s lives for centuries. The involvement of mutual cooperation and collective community efforts is a form of effort to maintain a clean environment, care for cultural heritage, and strengthen social ties among villagers. The ethnographic approach used in writing this article was carried out through interviews with several residents of Kandangan Village. Apart from that, this article also uses a qualitative approach which is supported by a literature study of scientific journals and theses, as well as an analysis of several YouTube channels that carry traditional mbeleh golekan content. The mbeleh golekan tradition is believed by the people to have existed and was carried out since the Majapahit era with the aim of being a ritual to repel reinforcements or danger. The implementation of this tradition is carried out by slaughtering dolls in the form of human babies, which are then buried at certain location points in Kandangan Village. The dolls that are slaughtered are substitutes for real human babies as sacrifices to repel reinforcements every month of Suro. The mbeleh golekan tradition is routinely carried out every year as a tribute of gratitude to the Danyang who opened the mat of the cage. It was as if it had to be carried out, because of the local people’s belief that if the mbeleh golekan tradition was not held, then a disaster would occur within a few days. Gratitude is also expressed through reading prayers or tahlil at each point of the procession, which is held a week before the peak of the event. The local community performs the mbeleh golekan and tahlilan rituals as a form of thanksgiving to Allah SWT.